Digital Technology Application Benefits and Impediments in Land Administration in South East Nigeria - Bike, I. J.; Emoh, F. I.; Oladejo, E. I. (International Journal of Real Estate, 2025)
This study is an assessment of the extent of service delivery benefits obtainable from digital technology application to land administration and the impediments in South East Nigeria. The study is anchored on the critical relevance of land administration to sustainable development, the place of digital technology application in defining the current global standard in land administration and the reality that local and national practices that significantly fall short of global standards are no longer acceptable in today’s world that has turned into a global village. Key service delivery benefits obtainable from digital technology application to land administration were identified and the extent of factors militating against their realization in the five states of south east Nigeria were assessed. Survey method was adopted in the study, using instrument of questionnaire. Purposive sampling technique was used, with sample size of 150 respondents involved, composed of land administration service providers comprising land officers, land surveyors, town planners and other support staff of the government ministries in charge of land administration in the states. Results revealed that the level of service delivery benefits obtainable from digital technology application to land administration is significant but the extent of factors militating against the application in the states is generally significant. The study concludes and recommends that in view of the significant benefits obtainable from digital technology application to land administration and the significant impediments to the application, therefore is urgent need for the states to remove all the existing impediments in order to migrate swiftly to a holistic Digital Land Administration System (DLAS) and be on current global best practices.